Imobilização da frutosiltransferase de Aspergillus oryzae IPT-301 em óxido de zinco para produção de frutooligossacarídeos - Megda, Fábio (2023)
Fructooligosaccharides (FOS) are prebiotic sugars and therefore beneficial to human health and nutrition. These sugars have a low caloric content and can be consumed by diabetic people, in addition to having great potential for application in the food industry, they can be substitutes for conventional sugars. The enzymatic synthesis of FOS occurs through the activity of transfructosylation (AT) in sucrose molecules, through the microbial enzyme fructosyltransferase (FTase, E.C. 2.4.1.9), and FTases can be produced from the fungus Aspergillus oryzae IPT-301 by submerged cell culture medium. Thus, this work aimed to study the immobilization of fructosyltransferase in pieces of zinc oxide (ZnO) through physical adsorption. The immobilization parameters in zinc oxide showed an immobilization yield of 38.00% and a recovered activity of 3.22%. The concentration effect study showed that the highest activity was achieved for a concentration of 600 g. L-1 of substrate, having fit to the Hill model. The pH stability test indicated that the biocatalyst has greater stability at pH between 6.0 and 6.5. The thermal stability of the biocatalyst was not significant compared to the soluble enzyme; therefore, it presented a half-life of 1.70 times that of the soluble enzyme at 30ºC. The immobilized enzyme showed storage stability with relative activity above 75% after 2 days. The physical-chemical characterization studies confirmed the immobilization of the enzyme on the surface of the support, corroborating with a satisfactory immobilization of the FTase.